2013
DOI: 10.2174/15733998113096660081
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Oils

Abstract: Many studies have demonstrated evidence of the health benefits of natural products. Plant extracts have been tested on a variety of physiological disorders, including diabetes mellitus. Studies have tested aqueous extracts, plant fractions extracts, families of active of compounds, and specific active compounds. In this review, we describe the antidiabetic effects of vegetable oils. Information was collected from ScienceDirect and PubMed databases using the following key words: Diabetes mellitus, Oils, Vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…It was found that cactus pier seeds oil, a natural product rich in unsaturated fatty acid [ 28 , 29 ], has antihyperglycemic property in diabetic rats [ 41 ]. Moreover, in the majority of studies on vegetable oils, it seems that they increase the tolerance to glucose in the different animal models following treatment in repeated doses, and this is by the regeneration of beta cells or the decrease of resistance to insulin [ 42 ]. Other studies have also shown an antihyperglycemic effect of different types of fixed oils (pomace olive oil) in the high-fat diet-fed mice [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that cactus pier seeds oil, a natural product rich in unsaturated fatty acid [ 28 , 29 ], has antihyperglycemic property in diabetic rats [ 41 ]. Moreover, in the majority of studies on vegetable oils, it seems that they increase the tolerance to glucose in the different animal models following treatment in repeated doses, and this is by the regeneration of beta cells or the decrease of resistance to insulin [ 42 ]. Other studies have also shown an antihyperglycemic effect of different types of fixed oils (pomace olive oil) in the high-fat diet-fed mice [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oils containing polyunsaturated fatty acids and antioxidants (tocopherols, polyphenols, and carotenoids, etc.) prevent diabetes complications, and may even inhibit the disease's development . In mice, the OFI oil clearly shows protective effects against chemically induced (alloxan) diabetes mellitus .…”
Section: Uses and Benefitsmentioning
confidence: 99%
“…Moreover, bioactive fatty acid methyl esters (FAMEs) including palmitic acid methyl ester, α-linolenic acid methyl ester and other benzene derivatives were characterized in M. dianthera. Some FAMEs were reported to have antidiabetic related activities [19] and palmitic acid was reported with potential α-amylase inhibitory activity [20]. Representative GC-spectra of the non-polar fractions (M1 and M2) of M. dianthera and the list of compounds found in the most active non-polar fractions are displayed in Figure 3 and Table 3 respectively.…”
Section: Gc-ms Analysis Of Fractionsmentioning
confidence: 99%